QRS Voltage-Duration Product in the Identification of Left Ventricular Hypertrophy in Spontaneously Hypertensive Rats - Bacharova,Ljuba (2002)
OBJECTIVE - Evaluation of the performance of the QRS voltage-duration product (VDP) for detection of left ventricular hypertrophy (LVH) in spontaneously hypertensive rats (SHR). METHODS - Orthogonal electrocardiograms (ECG) were recorded in male SHR at the age of 12 and 20 weeks, when systolic blood pressure (sBP) reached the average values of 165±3 mmHg and 195±12 mmHg, respectively. Age- and sex- matched normotensive Wistar Kyoto (WKY) rats were used as controls. VDP was calculated as a product of maximum QRS spatial vector magnitude and QRS duration. Left ventricular mass (LVM) was weighed after rats were sacrificed. RESULTS - LVM in SHR at 12 and 20 weeks of age (0.86±0.05 g and 1.05±0.07 g, respectively) was significantly higher as compared with that in WKY (0.65±0.07 g and 0.70±0.02 g). The increase in LVM closely correlated with the sBP increase. VDP did not reflect the increase in LVM in SHR. VDP was lower in SHR as compared with that in WKY, and the difference was significant at the age of 20 weeks (18.2mVms compared with 10.7mVms, p<0.01). On the contrary, a significant increase in the VDP was observed in the control WKY at the age of 20 weeks without changes in LVM. The changes in VDP were influenced mainly by the changes in QRSmax. CONCLUSION - LVM was not the major determinant of QRS voltage changes and consequently of the VDP. These data point to the importance of the nonspatial determinants of the recorded QRS voltage in terms of the solid angle theory.